Ethnobotanic knowledge of aborigines in Belum Forest area - Alang Md Rashid, Nahrul Khair; Yusof, Norimah; Abdul Rahim, Khairuddin; Mohd Ramli, Ros Anita; Kandar, Mohd. Zaidan; Awang, Mat Rasol; Osman, Mohd. Fajri; Abdul Rahman, Shyful Azizi; Abdul Wahab, Ahasanulkhaliqin (2010)
Aborigines have been living off the forests for ages. They must have also experienced sicknesses. The resources they have are just the forest. • The forests must also be the resources of ‘medicines’ – primarily plants. Even though the effectiveness is limited, may be due to administration rather than plants efficacy, their practices have been and still are very valuable in the development of some aspects of medicine. • Scientific study of the relationships between a community of people and plants in a particular area